Indonesia’s Digital Diplomacy: An Analysis of Penta-Helix Collaborative Governance - Muhammad Fachrie (Politicos: Jurnal Politik Dan Pemerintahan, 2025)
Digital diplomacy in Indonesia is run by a complicated governance structure that includes cooperation between government agencies and non-state actors. It mainly uses social media platforms and online media content to interact with audiences around the world, in contrast to traditional diplomacy, which depends on official state-to-state meetings. Through social media and other channel in internet, Indonesia actively used digital diplomacy to communicate with foreign entities during the COVID-19 pandemic. Despite its effectiveness during the pandemic, Indonesia's digital diplomacy governance is still largely unregulated and poorly understood. The purpose of this study is to investigate how Indonesian digital diplomacy ought to be managed with the participation of pertinent parties. The study investigates stakeholder dynamics in digital diplomacy using a qualitative methodology. It uses the penta-helix model of collaborative governance and the idea of digital diplomacy as its theoretical framework. Data triangulation is also used to improve the analysis's depth and dependability. In the end, the results indicate that both state and non-state actors should be a part of Indonesia's digital diplomacy governance, with the government serving as a catalyst and a regulator. The government is obligated to collaborate with the media, industry, academia, and civil society organizations (CSOs). MoFA's strategic planning for 2017 and 2020–2024, government collaboration with various businesses, university discussions on digital diplomacy (such as ITB, UGM and UI), FPCI's role as a CSO, and Kompas and the Jakarta Post's coverage of Indonesia's diplomatic interest are some examples of best practices in the country's digital diplomacy. However, the absence of comprehensive regulation remains a major obstacle to Indonesia's digital diplomacy. The study concludes by highlighting the necessity of a thorough and well-coordinated strategy that capitalizes on the advantages of each of the five penta-helix actors in order to improve the efficacy of digital diplomacy in a world that is becoming more and more digitalized.